Relationship between family functionality and the quality of life of the elderly - Edison Vitório de Souza Júnior; Eduarda Raquel Viana; Diego Pires Cruz; Cristiane dos Santos Silva; Randson Souza Rosa; Lais Reis Siqueira; Namie Okino Sawada (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: To analyze the correlation between family functionality and the quality of life of the elderly. Method: Sectional and correlational study conducted with 692 Brazilian elderly between July and October 2020. The elderly filled three instruments: biosociodemographic, family APGAR and WHOQOL-Old. The tests Kruskal-Wallis, Pearson correlation, and linear regression analyzed the data. The study considered a 95% confidence interval (p < 0.05) for all analyses. Results: The elderly with mild and severe family dysfunction presented worse quality of life when compared to the elderly with a functional family. All facets of quality of life correlated positively with family functionality. Conclusion: Family functionality is positively correlated with the quality of life of the elderly, therefore requiring the inclusion of the family in health care plans to identify potential family stressors early and plan interventions to solve the problems raised.